Bioinspired and Biomimetic Nanomedicines for Targeted Cancer Therapy - Xiaoqiu Xu; Tong Li; Ke Jin (Pharmaceutics, 2022)
Undesirable side effects and multidrug resistance are the major obstacles in conventional chemotherapy towards cancers. Nanomedicines provide alternative strategies for tumor-targeted therapy due to their inherent properties, such as nanoscale size and tunable surface features. However, the applications of nanomedicines are hampered in vivo due to intrinsic disadvantages, such as poor abilities to cross biological barriers and unexpected off-target effects. Fortunately, biomimetic nanomedicines are emerging as promising therapeutics to maximize anti-tumor efficacy with minimal adverse effects due to their good biocompatibility and high accumulation abilities. These bioengineered agents incorporate both the physicochemical properties of diverse functional materials and the advantages of biological materials to achieve desired purposes, such as prolonged circulation time, specific targeting of tumor cells, and immune modulation. Among biological materials, mammalian cells (such as red blood cells, macrophages, monocytes, and neutrophils) and pathogens (such as viruses, bacteria, and fungi) are the functional components most often used to confer synthetic nanoparticles with the complex functionalities necessary for effective nano-biointeractions. In this review, we focus on recent advances in the development of bioinspired and biomimetic nanomedicines (such as mammalian cell-based drug delivery systems and pathogen-based nanoparticles) for targeted cancer therapy. We also discuss the biological influences and limitations of synthetic materials on the therapeutic effects and targeted efficacies of various nanomedicines.